External Funds and Sustainable Development in Rwanda: A Public Perspective (2015-2024) - Obiora Peters, Emeka (INTERNATIONAL JOURNAL OF SOCIAL SCIENCES AND MANAGEMENT RESEARCH, 2026)
This study assessed the impact of external funding on sustainable development in Rwanda from the public perspective. Specifically to; assess public perception on external funds for sustainable development, analyse the relationship between external funds and sustainable development & examine the challenges and opportunities associated with external funds for sustainable development. A mixed method strategy wherein a quantitative research design, specifically a survey design was adopted. A sample size of 100 was obtained from a population of 13,246,394 using Solven’s formula. The findings are that perception on external funds (0.000), governance quality (0.001), Human capital (0.000) & infrastructure (0.000) is perceived to significantly affect sustainable development; whereas environmental funding (0.072) have no significant impact on sustainable development in Rwanda. The study concludes that external funds significantly contribute to sustainable development in Rwanda. The study recommends enhanced transparency and Public involvement in aid utilization; Strengthen institutional and governance Capacity, prioritize human capital investment, align aid with National infrastructure plans, integrate environmental sustainability in aid programming, reduce overdependence and enhanced domestic resource mobilization.